The majestic virtues of writing in Aurelia by Gerard de Nerval - El Bahi, Abderrahim (Romanica Olomucensia, 2022)
The present work aims to address, in the light of a critical reading of Aurelia, the question of writing, envisaged as an ``artistic work'' of free imagination, a ``sublimatory activity'' of the constraints of the world, and which functions as a mechanism of psychological compensation for the author's reality and as a motor of psychic liberation from individual tensions. To understand the implications of this concept, it has been drawn a critical paradigm from a multilateral concept of literature and literary texts, which are perceived as the point of the intersection of several approaches. To do this, on the basis of certain biographical, narrative, and aesthetic data, two complementary functions of the ``pain'' at work in Aurelia are examined: the function 'constituent' and the function 'instituting'. Indeed, de Nerval's experience of pain proves to be particularly ``fruitful'', ``productive'', ``suggestive'', even ``evocative'', since it seems to have a singular effect on his aesthetic sensitivity to the point of constituting a first vocation of writing and a source of poetic inspiration, and consequently finds a more ardent appeasement in writing. Nevertheless, in addition to being ``constituent'', pain acquires a symbolically ``subversive'' status, ``instituting'' in the Nervalian narrative: it imposes itself by opposing and is essentially transformative of reality by imagination and the founder of the aesthetic enterprise of the work, shared between the psychosis of the author and the echo that it finds in the fictional universe of the story.
Keywords: Aurelia; pain; writing; aesthetic; Gerard de Nerval; suffering; sublimation